The Danish way of parenting : what the happiest people in the world know about raising confident, capable kids - Alexander, Jessica Joelle; Sandahl, Iben (TarcherPerigee Book, 2016)
What makes Denmark the happiest country in the world--and what are the secrets of Danish parents for raising happy, confident, succesful kids, year after year? This upbeat and practical guide brings together the insights of a licensed psychotherapist and a mom -- a Dane and an American married to a Dane, respectively -- on the habits of the happiest families on earth.